Early predictors of psychosocial functioning 5 years after paediatric stroke. (17th August 2017) - Greenham, Mardee; Anderson, Vicki; Cooper, Anna; Hearps, Stephen; Ditchfield, Michael; Coleman, Lee; Hunt, Rod W; Mackay, Mark T; Monagle, Paul; Gordon, Anne L
Abstract : Aim: Little is known about psychological and social outcomes after paediatric stroke. This study aimed to evaluate psychosocial outcomes in children 5 years after paediatric stroke and explore the contribution of early presenting factors. Method: Thirty‐one children (19 males, 12 females) with arterial ischemic stroke were involved in this prospective, longitudinal study. Children underwent intellectual assessment at 12 months poststroke and parents completed questionnaires rating their own mental health and their child's functioning at 12 months and 5 years poststroke. Results: At 5‐year follow‐up, psychological and social function were significantly poorer than normative expectations. Exploration of early predictive factors showed poorer cognitive and psychological function at 12 months poststroke and older age at stroke onset was associated with poorer psychosocial function at 5 years. Larger lesion size was also associated with poorer psychological function at 5 years poststroke. Interpretation: These early predictors of poorer psychosocial outcome suggest that screening children within the first year after stroke may identify children most at risk of later problems and facilitate early intervention. What this paper adds: Psychosocial function is impaired in children 5 years poststroke. Children with neonatal onset stroke have better psychosocial outcomes at 5 years poststroke than later onset. Poorer psychological and cognitive function at 12 months poststroke is associated the poorer psychological function at 5 years. This article is commented on by Westmacott on pages991–992 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.